2002
DOI: 10.1101/lm.47602
|View full text |Cite
|
Sign up to set email alerts
|

Eyeblink Classical Conditioning and Interpositus Nucleus Activity Are Disrupted in Adult Rats Exposed to Ethanol as Neonates

Abstract: Neonatal exposure to ethanol in rats, during the period of brain development comparable to that of the human third trimester, produces significant, dose-dependent cell loss in the cerebellum and deficits in coordinated motor performance. These rats are also impaired in eyeblink conditioning as weanlings and as adults. The current study examined single-unit neural activity in the interpositus nucleus of the cerebellum in adults following neonatal binge ethanol exposure. Group Ethanol received alcohol doses of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
47
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 50 publications
17
47
1
Order By: Relevance
“…Rat pups exposed to binge-like levels of ethanol across PD 4-9 are impaired in eyeblink conditioning, both as weanlings (Stanton and Goodlett, 1998;Tran et al, 2005) and adult rats (Green et al, 2002a;Green et al, 2002b;Green et al, 2000). In addition to their behavioral deficits, adult rats exposed as neonates to alcohol have up to 50% fewer cerebellar deep nuclear neurons (Green et al, 2002b), as well as a corresponding reduction in learning-related neural activity in the IP (Green et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat pups exposed to binge-like levels of ethanol across PD 4-9 are impaired in eyeblink conditioning, both as weanlings (Stanton and Goodlett, 1998;Tran et al, 2005) and adult rats (Green et al, 2002a;Green et al, 2002b;Green et al, 2000). In addition to their behavioral deficits, adult rats exposed as neonates to alcohol have up to 50% fewer cerebellar deep nuclear neurons (Green et al, 2002b), as well as a corresponding reduction in learning-related neural activity in the IP (Green et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their behavioral deficits, adult rats exposed as neonates to alcohol have up to 50% fewer cerebellar deep nuclear neurons (Green et al, 2002b), as well as a corresponding reduction in learning-related neural activity in the IP (Green et al, 2002a). One issue that makes interpretation of these results potentially problematic, however, is that the intensity of the periorbital shock US was independently titrated for each subject in order to produce a defined conditioned responsemaking it difficult to establish if US intensity was a major factor in determining the ethanolmediated conditioning deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental alcohol-induced structural damage to the cerebellum and correlated deficits in acquisition of eyeblink conditioning were first demonstrated in rats following binge-like exposure to alcohol during the "brain growth spurt" of the early postnatal period (Green, 2004;Green, Johnson, Goodlett, & Steinmetz, 2002;Green, Rogers, Goodlett, & Steinmetz, 2000;Green, Tran, Steinmetz, & Goodlett, 2002;Stanton & Goodlett, 1998;Tran, Stanton, & Goodlett, 2007 , 1997). Taken together, these findings suggest that cerebellar damage and deficits in cerebellar-dependent learning may be a common phenotype of the fetal alcohol spectrum disorder (FASD) that results from heavy prenatal alcohol exposure (Riley & McGee, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For acquisition of trace conditioning and other higher-order procedural variants, the hippocampus and related forebrain structures are additionally required (Ivkovich & Stanton, 2001;McGlinchey-Berroth, Carrillo, Gabrieli, Brawn, & Disterhoft, 1997;Solomon, Vander Schaaf, Thompson, & Weisz, 1986;Weiss, Bouwmeester, Power, & Disterhoft, 1999). The developmental emergence of eyeblink conditioning has been characterized in rodents and humans (Claflin, Stanton, Herbert, Greer, & Eckerman, 2002;Freeman, Carter, & Stanton, 1995;Freeman, Barone, & Stanton, 1995;Ivkovich, Paczkowski, & Stanton, 2000, Freeman, Spencer, Skelton, & Stanton, 1993Stanton, Freeman, & Skelton, 1992), including characterization of correlated developmental changes in structure and function of identified eyeblink conditioning neural circuits (Freeman & Muckler, 2003;Freeman & Nicholson, 2000a, 2000b, suggesting that eyeblink conditioning may be a useful tool as an early indicator of prenatal brain damage in translational research.Developmental alcohol-induced structural damage to the cerebellum and correlated deficits in acquisition of eyeblink conditioning were first demonstrated in rats following binge-like exposure to alcohol during the "brain growth spurt" of the early postnatal period (Green, 2004;Green, Johnson, Goodlett, & Steinmetz, 2002;Green, Rogers, Goodlett, & Steinmetz, 2000;Green, Tran, Steinmetz, & Goodlett, 2002;Stanton & Goodlett, 1998;Tran, Stanton, & Goodlett, 2007 , 1997). Taken together, these findings suggest that cerebellar damage and deficits in cerebellar-dependent learning may be a common phenotype of the fetal alcohol spectrum disorder (FASD) that results from heavy prenatal alcohol exposure (Riley & McGee, 2005).…”
mentioning
confidence: 99%
“…Impaired contextual conditioning, Identification of a learning/memory deficit in adult offspring demonstrates that the mouse, as well as the previously described rat, FAE model produces learning and memory impairments which persist into adulthood, similar to the clinical course of FASD in humans. It is interesting to note that Green et al (2002) reported that eyeblink delay conditioning is impaired in rats that were exposed to alcohol as neonates, approximating the human third trimester period. Thus, FAE-induced deficits in associative learning measured using delay conditioning paradigms are reproducible across species and appear to be a useful behavioral endpoint for the study of the effects of therapeutic interventions on FAE-induced learning and memory deficits.…”
Section: Eifect Of Saccharin Fading Ethanol Exposure Paradigm On Delamentioning
confidence: 99%